2007
DOI: 10.1213/01.ane.0000252458.20912.ef
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Minimum Local Anesthetic Volumes and Doses of Epidural Bupivacaine (0.125% w/v and 0.25% w/v) for Analgesia in Labor

Abstract: Bupivacaine 0.125% (w/v) when compared with 0.25% (w/v) produced equivalent analgesia with a 50% increase in volume, but with a 25% reduction in dose. Any reduction in dose, without loss of efficacy, reduces risk of toxicity and improves safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…This may have some influence on labor analgesic outcomes, since larger boluses of more dilute LA may have improved spread in the epidural space, resulting in enhanced analgesia of longer duration and increased patient satisfaction 15,16 . Thus, while our current results differed from what has been shown in previous reports, the conclusions must be interpreted in the context of these potential differences.…”
Section: Discussionmentioning
confidence: 99%
“…This may have some influence on labor analgesic outcomes, since larger boluses of more dilute LA may have improved spread in the epidural space, resulting in enhanced analgesia of longer duration and increased patient satisfaction 15,16 . Thus, while our current results differed from what has been shown in previous reports, the conclusions must be interpreted in the context of these potential differences.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that longer lockout times with no background infusion or small bolus doses may not allow the agents to disperse adequately; several investigations have indicated that the dose and volume of the bolus injection is important for effective PCEA labor analgesia. 16,17 Furthermore, longer lockout times may induce more frequent bolus demands without delivery of agents because the request occurred within the lockout time interval. 14 With the agents and doses used in our study, a 10-min lockout interval when using a continuous background infusion may represent optimal settings for labor analgesia without increasing the total local anesthetic and opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…[24] in their comparative study sought to determine the minimum local analgesic volume (MLAV) and minimum local analgesic dose (MLAD) of an initial bolus of epidural bupivacaine 0.125% and 0.25%. The MLAV of bupivacaine 0.125% was 13.6 ml (95% CI 12.4–14.8) versus 9.2 ml (95% CI 6.9–11.5) for bupivacaine 0.25% ( P = 0.002).…”
Section: Technical Advancesmentioning
confidence: 99%